The Theoretical Solving of Intersection Point of the Horizontal and Vertical Gravity Gradients in Order to Estimate the Depth of Causative Source of Gravity Anomaly - Al-Banna, Ahmed S.; Ali, Kamal K. (Iraqi Journal of Science, 2022)
The depth of causative source of gravity is one of the most important parameterof gravity investigation. Present study introduces the theoretical solve of theintersection point of the horizontal and vertical gradients of gravity anomaly. Twoconstants are obtained to estimate the depth of causative source of gravity anomaly,first one is 1.7807 for spherical body and the second is 2.4142 for the horizontalcylinder body. These constants are tested for estimating the depth of three actualcases and good results are obtained. It is believed that the constants derived ontheoretical bases are better than those obtained by empirical experimental studies.